Circulating immune complexes in acute rheumatic carditis - Sprenger, Kenneth John (Department of Paediatrics and Child Health, 2018)
The group A beta-haemolytic streptococcus is known to be the aetiologic agent in acute rheumatic fever, but the exact pathogenesis remains obscure. A review of the histopathology of the Aschoff body suggests that the cardiac pathology is a granulomatous hypersensitivity reaction. However the streptococcus has not been found in the lesions, and the agent responsible for the granuloma has not yet been identified. Circulating immune complexes have previously been measured in some children with acute rheumatic fever. The normal or raised complement components measured by some workers in acute rheumatic fever suggests that the immune complexes may not be complement fixing. Considering that the usual assays for measuring immune complexes depend on complement fixation, the failure of the immune complexes to fix complement might produce false negative results. A physical, non-complement fixing assay (polyethylene glycol precipitation - PEG), was therefore used to measure circulating immune complexes. Results were expressed as total IgG precipitated (g/L), or as a percentage of serum IgG. Immune complexes were also measured by two complement dependent assays, a Clq binding assay (ClqBA), and conglutinin binding assay (CBA). Complexes were assayed in 15 children with acute rheumatic carditis (ARC), 11 with non-active, chronic rheumatic heart disease (CRHD), 13 with acute poststreptococcal glomerulonephritis (APSGN), and 15 normal children and adults (NORMAL). Total haemolytic complement, complement components as well as the complement breakdown product C3d, were measured.